Konsep Kinerja dalam Perspektif Islam: Sebuah Telaah Pustaka - Agus Faisal Asyha (Journal of Literature Review, 2025)
Islamic education emphasizes not only academic achievement but also character formation and moral integrity. One crucial aspect of Islamic education is the concept of performance, which, in the Islamic perspective, is measured not solely by tangible results but also by the intention, sincerity, and actions performed to gain the pleasure of Allah. This study aims to identify and analyze the concept of performance in Islam, as well as its application in the management of Islamic education. This literature review adopts a thematic and qualitative analysis approach, collecting relevant literature from the Qur'an, Hadith, and previous studies. The findings suggest that performance in Islam involves two dimensions: measurable worldly achievements and the quality of deeds grounded in intention and noble character. This concept provides new insights into the management of Islamic education, emphasizing that good performance must balance both worldly and hereafter achievements. In conclusion, the application of Islamic-based performance principles in educational management can strengthen students' character and enhance the quality of Islamic education holistically.